Antibacterial Properties of Bacterial Cellulose-Quercetin Composite Membrane - Riza Apriani; Asman Sadino; Astri Senania; Zahara Oetari; Gania Ningsih Noer Fajrianti (Chemistry Department, Faculty of Sciences and Mathematics, Diponegoro University, 2024)
Bacterial cellulose has been thoroughly explored as a biomaterial for various applications due to its intrinsic mechanical, physical, and biological features. Its structural characteristics provide ideal conditions for developing composite, expanding its range of applications even further. The current study aims to synthesize quercetin-loaded bacterial cellulose composite as a potential wound dressing by utilizing the antibacterial activity of quercetin and the unique characteristics of bacterial cellulose. The produced bacterial cellulose was ex-situ modified with quercetin. The composite was characterized for its functional group by FTIR, its morphology by FE-SEM, and its antibacterial activity was evaluated against Gram-positive S. aureus and Gram-negative E. coli through the disc diffusion method. Characterization analyses confirmed the successful impregnation of quercetin into the BC matrix. The antibacterial activity of BC-Quercetin showed moderate activity, both against S. aureus and E. coli. Determining the loading dose of quercetin into bacterial cellulose is a gap for conducting future research. However, this study indicates that combining bacterial cellulose with quercetin could provide a base for developing promising alternatives for the conventional dressing system in wound healing.